2021
DOI: 10.3390/jcm10071450
|View full text |Cite
|
Sign up to set email alerts
|

Statin Use Is Associated with a Decreased Risk of Mortality among Patients with COVID-19

Abstract: Background: Recent epidemiological studies remain controversial regarding the association between statin use and reducing the risk of mortality among individuals with COVID-19. Objective: The objective of this study was to clarify the association between statin use and the risk of mortality among patients with COVID-19. Methods: We conducted a systematic articles search of online databases (PubMed, EMBASE, Scopus, and Web of Science) between 1 February 2020 and 20 February 2021, with no restriction on language… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 46 publications
1
11
0
Order By: Relevance
“…The reason why studies may show a difference in outcome for statin users vs non statin users may relate to differences in the level of risk in the groups studied. For example, the Coronado study [ 5 ] described a higher mortality rate in statin users whereas other studies have described a relative protective effect of statins in COVID-19-affected individuals with T2DM [ 35 ]. There is no question that statin use is overall hugely beneficial as reported in a recent very large study on US veterans [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The reason why studies may show a difference in outcome for statin users vs non statin users may relate to differences in the level of risk in the groups studied. For example, the Coronado study [ 5 ] described a higher mortality rate in statin users whereas other studies have described a relative protective effect of statins in COVID-19-affected individuals with T2DM [ 35 ]. There is no question that statin use is overall hugely beneficial as reported in a recent very large study on US veterans [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Statin-associated improved prognosis is partially attributed to the relieved inflammatory response [102]. A number of other researchers have confirmed the beneficial role of statin-use in COVID-19 infection [103][104][105][106][107][108][109][110][111]. Of note, an updated meta-analysis of 22 studies suggested stains use in COVID-19 patients were connected to an approximately 35% decrease in the adjusted risk of mortality [112].…”
Section: Cholesterol Metabolismmentioning
confidence: 96%
“…Most studies originated from China, and a few recent meta-analyses showed the reflection of statin effects in the European and North American patient population. However, the findings and results varied greatly in study size, varying types, and dose of statin regimes [ 29 , 64 ]. With the results in the previous observational studies and the significant inference from the present study, the results of the progressing clinical trials will be critical.…”
Section: Discussionmentioning
confidence: 99%